(3GOGQI GdeDSSGJ (B:s (3ef GdcJGHGJ GdfXQjI Gdi GdeeGQSGJ GdejOGfjI (B/s - (3YeGQI, eMeO eMeO LGH Gddgs; (3SGde, eMeO fHjd SYO s ((3GdbGgQI(B: s (3OGQ GdWHGYI GdMQI(B, s, 2005)
(3GHYGO GOGQI GdehGQO GdHTQjIh cPG GdJNWjW dGOGQI GdehGQO GdHTQjI GVGaI Gdi GdGNUGFj GdGLJeGYj cGOGQj h GOGQI GdgjFGJ GdMchejI h GdGgdjI h GdQbGHI GdGOGQjI h GdGJLGgGJ GdMOjKI aj GdGOGQIs
(3eQGLY U(B.341 , (3edGMb U(B.353s
Keywords: (3GOGQI GdeDSSGJs; (3GOGQI GdehGQO GdHTQjIs